2016
DOI: 10.1212/wnl.0000000000002673
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of white matter hyperintensity burden in patients with Fabry disease

Abstract: Objective: Using a semiautomated volumetric MRI assessment method, we aimed to identify determinants of white matter hyperintensity (WMH) burden in patients with Fabry disease (FD).Methods: Patients with confirmed FD and brain MRI available for this analysis were eligible for this protocol after written consent. Clinical characteristics were abstracted from medical records. T2 fluid-attenuated inversion recovery MRI were transferred in electronic format and analyzed for WMH volume (WMHV) using a validated, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 29 publications
2
33
1
Order By: Relevance
“…Nevertheless, 8% had a previous stroke, which is a similar proportion to previous studies. 10 Contrary to previous studies, 8 , 10 we found no association between history of stroke and WMH progression in FD. Furthermore, we found no association between hypertension, smoking, or diabetes and WMH progression in FD.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, 8% had a previous stroke, which is a similar proportion to previous studies. 10 Contrary to previous studies, 8 , 10 we found no association between history of stroke and WMH progression in FD. Furthermore, we found no association between hypertension, smoking, or diabetes and WMH progression in FD.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, prior ERT exposure has been associated with reduced WMH volume in 31- to 40-year-old patients on cross-sectional analysis. 10 Other previous studies evaluating the rate of WMH progression while on ERT have reported conflicting results. 3 , 5 , 30 32 While a randomized controlled trial would be needed to test definitively the relationship between ERT and WMH progression, such a trial might not be achievable given the widespread use of ERT in clinical practice and the lack of clinical equipoise regarding the efficacy of ERT in treating cardiac or renal complications of FD.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Anderson-Fabry Disease (FD) is a rare X-linked lysosomal storage disorder caused by deficient activity of the enzyme ␣-galactosidase A (␣-GAL A), resulting in progressive and diffuse lysosomal accumulation of neutral glycosphingolipids, especially globotriaosylceramide (Gb3) in vascular endothelium, kidneys, heart, brain, skin, cornea and other tissues leading to multiorgan damage [1]. Transient ischemic attacks (TIAs), strokes [2] and brain white matter lesions (WML) [3] are common central nervous system (CNS) manifestations. In recent years there has been growing body of evidence supporting a link between the pathogenesis of PD and lysosomal dysfunction, namely in Gaucher disease (GD) and FD.…”
Section: Introductionmentioning
confidence: 99%